Penanaman Pendidikan Karakter Dalam Pembelajaran PAI di SMP Negeri 12 Palembang - Aida Imtihana; Faisal Faisal; Wasilah Wasilah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This research is entitled "Inculcation of Character Education in PAI Learning in SMP N 12 Palembang". This study aims to determine the inculcation of character education in PAI learning in schools and the supporting factors and inhibiting factors in inculcating character education in PAI learning in schools. The type of research used in this research is qualitative research. Data collected through observation, interviews, and documentation. This type of research approach is descriptive qualitative. The techniques used in data analysis are data reduction, data presentation and drawing conclusions. Test the validity of this research data using method triangulation and source trianulation. In this study it was found that pie learning at this school was carried out face-to-face where previously it was done online. So that the findings in this study are PAI teachers find that students' technological abilities are getting better. But sometimes in the learning process sometimes become lazy and not disciplined with time. So that in PAI learning at school, PAI teachers instill four positive values ​​in learning that will have an impact on student character. The four values ​​are honesty, discipline, hard work and wisdom.